Architectural features of the Mahishasuramardini Temple (Temple 9) - Temples of India Project Team (Jio Institute, 2024)
The temple features a well-defined pitha (a small platform) and vedibandha (basal mouldings). Its walls are plain, adorned with pilasters topped by the grassamukha (face of glory) band. The shikhara (superstructure) is severely damaged.